The Influence of Corporate Social Responsibility Towards Employees on Performance: A Comparison of Companies on The Indonesian Stock Exchange - Dina Madinah; Mara Ridhuan Che Abdul Rahman; Shifa Mohd Nor; Mohd Rizal Palil (FEB Universitas Sultan Ageng Tirtayasa, 2023)
Ullmann’s (1985) Stakeholder theory states that the implementation of Corporate Social Responsibility (CSR) has an influence on the achievement of a company’s economic performance. This research examines the influence of CSR on employees (CSR-E) including the salary and welfare, education, work safety and gender equality on sales growth and human resource efficiency. This research compares three types of perusahaanes, namely natural resource, manufacture, and service perusahaanes listed on the Indonesian Stock Exchange. It is hoped that the results of this research can provide a solution regarding the importance of implementing CSR-E and its influence on companies’ business performance, so that companies are much more motivated to implement CSR-E. This research uses descriptive and quantitative data analysis techniques where SPSS application was used to analyze 297 annual and financial reports of companies listed on the Indonesian Stock Exchange from 2015, 2016 and 2017. The research found that CSR-E for work safety had an influence on human resource efficiency in manufacturing companies and CSR-E salary and gender equality had a significant influence on sales growth and natural resource efficiency in service-based companies. Implementing CSR-E is an important requirement for manufacturing and service companies. It is because manufacturing and service perusahaanes are companies with a high risk of pollution and work accident rates. The controlled variable for the number of workers has an influence on sales growth and human resource efficiency. Workers are the substantial party for the company because they are directly involved in the daily basis company’s operational activities in an effort to achieve the company’s financial performance.